#### Answer

(7, -3)

#### Work Step by Step

Write the first equation as a solution for x in terms of y:
2x + 5y = -1
2x = -5y - 1
x = $-\frac{5}{2}y - \frac{1}{2}$
Substitute x in the second equation with the equation in terms of y and solve for y:
3($-\frac{5}{2}y - \frac{1}{2}$) - 4y = 33
$-\frac{15}{2}y - \frac{3}{2}$ - 4y = 33
$-\frac{23}{2}y = \frac{69}{2}$
y = -3
Let y = -3 in the first equation to solve for x:
x = ($-\frac{5}{2})(-3) - \frac{1}{2}$
x = 7
Check the solution (7, -3) in the second equation:
3(7) - 4(-3) = 33
21 + 12 = 33
33 = 33; True